Safety and efficacy of concurrent immune checkpoint inhibitors and hypofractionated body radiotherapy. (3rd July 2018) - Mohamad, Osama; Diaz de Leon, Alberto; Schroeder, Samuel; Leiker, Andrew; Christie, Alana; Zhang-Velten, Elizabeth; Trivedi, Lakshya; Khan, Saad; Desai, Neil B; Laine, Aaron; Albuquerque, Kevin; Iyengar, Puneeth; et al.
ABSTRACT: Integration of hypofractionated body radiotherapy (H-RT) into immune checkpoint inhibitor (ICI) therapy may be a promising strategy to improve the outcomes of ICIs, although sufficient data is lacking regarding the safety and efficacy of this regimen. We, hereby, reviewed the safety and efficacy of this combination in 59 patients treated with H-RT during or within 8 weeks of ICI infusion and compared results with historical reports of ICI treatment alone. Most patients had RCC or melanoma. Median follow-up was 11 months. Most patients received either Nivolumab alone or with Ipilimumab; 83% received stereotactic RT and 17% received conformal H-RT. Any grade adverse events (AEs) were reported in 46 patients, and grade 3–4 in 12 patients without any treatment-related grade 5 toxicity. The most common grade 3 AEs were fatigue and pneumonitis. Grade 3–4 toxicities were higher with ICI combination and with simultaneous ICIs. Overall, most any-grade or grade ≥3 AE rates did not differ significantly from historically reported rates with single-agent or multi-agent ICIs. Toxicity did not correlate with H-RT site, dose, fraction number, tumor type, or ICI and H-RT sequencing. Median progression-free survival was 6.5 months. Objective response rate (ORR) was 26%; 10% had complete response (CR). Median duration of response was 9.4 ± 4.6 months. H-RT of lung lesions was more likely to achieve CR than other sites. H-RT of bone lesions had a lower ORR than non-bone H-RT. In conclusion, combining body H-RT with ICIs is safe and promising. Prospective validation is warranted.